Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA - Orfinger, Alexander B.; Etnier, David A. (Zootaxa, 2020)
We describe here a new caddisfly species of the genus Polycentropus (Trichoptera: Polycentropodidae) based on males from numerous localities throughout the southern Appalachian Mountains of the United States. Polycentropus dinkinsorum is a member of the P. confusus Species Group and is readily separated from its congeners based on aspects of the male genitalia. A diagnosis and illustrations of male genitalia are provided. In addition, P. pentus Ross 1941 is reported for the first time from the Canadian province of Newfoundland and Labrador.